2016
DOI: 10.1080/14767058.2016.1192602
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intravenous ferrous sucrose and oral ferrous sulphate in treatment of postpartum iron deficiency anemia

Abstract: Intravenous ferrous sucrose increases Hb level more rapidly than ferrous sulphate in women with postpartum IDA. It also replenishes iron stores more rapidly with better tolerability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 18 publications
0
21
0
2
Order By: Relevance
“…Fifteen randomized trials met our inclusion criteria. [18][19][20][21][22][32][33][34][35][36][37][38][39][40][41] Reasons for excluding the remaining 17 studies are described in Appendix 2. Our study cohort comprised 2182 women, with 1001 and 1181 women receiving oral iron and IV iron therapy, respectively.…”
Section: Data Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…Fifteen randomized trials met our inclusion criteria. [18][19][20][21][22][32][33][34][35][36][37][38][39][40][41] Reasons for excluding the remaining 17 studies are described in Appendix 2. Our study cohort comprised 2182 women, with 1001 and 1181 women receiving oral iron and IV iron therapy, respectively.…”
Section: Data Synthesismentioning
confidence: 99%
“…21 Fourteen trials consisted of 2 treatment arms (oral and IV iron). One study had 3 treatments arms 22 ; 2 arms comprised IV iron preparations (ferrous sucrose and ferrous carboxymaltose, respectively), and 1 arm comprised oral Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) flowchart for studies identified and excluded (included studies [18][19][20][21][22][32][33][34][35][36][37][38][39][40][41] 22 Two studies included women with other comorbid disease. 22,40 One study excluded women with known nutritional disorders.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two of these studies have shown significant improvement in hemoglobin levels on posttreatment day 14 from intravenous iron, but these differences were modest. In absolute terms, there was a smaller increase in hemoglobin of 1.4-1.5 g/dL in those receiving oral iron as compared with 2.0-3.8 g/dL in those receiving intravenous iron (109,111). At posttreatment day 40-42 none of the studies demonstrated a difference in hemoglobin level or any other clinical outcomes between oral or intravenous iron.…”
Section: Cell Salvagementioning
confidence: 97%
“…When a blood transfusion is not necessary, but supplemental iron is indicated, the use of intravenous iron (ferrous sucrose) has been compared to oral iron for postpartum anemia in a few small randomized controlled trials. (109)(110)(111)(112). Two of these studies have shown significant improvement in hemoglobin levels on posttreatment day 14 from intravenous iron, but these differences were modest.…”
Section: Cell Salvagementioning
confidence: 99%